Dynamic 18F-FLT PET imaging of spatiotemporal changes in tumor cell proliferation and vasculature reveals the mechanistic actions of anti-angiogenic therapy. (27th July 2018) - Scarpelli, Matthew; Simoncic, Urban; Perlman, Scott; Liu, Glenn; Jeraj, Robert
Abstract: Anti-angiogenic therapies target tumor vasculature and tumor cells, thus a concurrent assessment of these targets would lead to a greater understanding of therapeutic resistance and facilitate development of improved therapeutic strategies. We utilize dynamic 3′-deoxy-3′- 18 F-fluorothymidine positron emission tomography ( 18 F-FLT PET) scanning to concurrently assess changes in tumor cell proliferation and vasculature during anti-angiogenic therapy, providing insight into how these therapies may be used effectively with combination chemotherapy. Thirty-three patients with advanced solid malignancies underwent treatment with vascular endothelial growth factor receptor inhibitor (VEGFR-TKI) axitinib on an intermittent schedule (two-weeks-on/one-week-off). Patients had up to three dynamic 18 F-FLT PET/CT scans: at baseline, after two weeks of continuous VEGFR-TKI treatment, and following a one week treatment break. 18 F-FLT kinetics were analyzed using a two-tissue compartment kinetic model. Kinetic parameters V b and K 1 were extracted to quantify changes in tumor vasculature and the 18 F-FLT flux constant K i was calculated to quantify changes in tumor cell proliferation. Two weeks of continuous axitinib exposure led to decreases in V b (median −21%, P   =  0.07), K 1 (median −39%, P   <  0.01), and K i (median −37%, P   <  0.01), corresponding to diminished tumor vasculature and cell proliferation that may antagonize treatment with concurrent chemotherapy. Axitinib treatment breaks led to significant increases in V b (median  +42%, P   <  0.01), K 1 (median  +46%, P   <  0.01), and K i (median  +39%, P   <  0.01) that is suggestive of an optimal time to schedule synergistic chemotherapy. Significant negative correlations (rho  ⩽  −0.70, P   <  0.01) were found between changes in tumor vasculature during axitinib exposure weeks and changes in tumor vasculature during treatment breaks. Imaging with dynamic 18 F-FLT PET revealed new insights relating to the interplay of vascular and proliferative pharmacodynamics of axitinib therapy, facilitating a greater understanding of the mechanistic actions of VEGFR-TKIs. Increases in tumor vasculature and cell proliferation during VEGFR-TKI treatment breaks, suggests this period is an optimal time to schedule synergistic chemotherapy and warrants further investigation.